The Effect of Empowering Leadership on Innovative Work Behavior: The Mediating Role of Knowledge Sharing - Aghnia Ghassani, Ghina; Indriati, Fibria (Pelopor Publikasi Akademika, 2024)
Institutional transformation in Indonesia changes the structure, culture, and work processes of an organization to be more responsive to change, able to innovate, and achieve high performance. Innovative work behavior has become one of the important factors for organizations to survive in the midst of a dynamic and competitive environment. In this regard, it is necessary to analyze the factors that can influence innovative work behavior so that it can be used as empirical evidence for organizational development policy recommendations and work processes. This study aims to analyze the influence between empowering leadership, knowledge sharing, and innovative work behavior. The study was conducted on 57 employees in the Secretariat Work Unit of the Ministry of State Secretariat which has a total of 447 employees. The research approach used is a quantitative positivism approach with data collection techniques through surveys using questionnaires as research instruments. The data obtained from the questionnaire results were analyzed using IBM SPSS Statistics program version 25 through the Partial T test to determine the influence between certain variables and Hierarchical Multiple Regression to test the role of mediating variables in the relationship between independent variables and dependent variables. The results showed that the relationship of empowering leadership to innovative work behavior, empowering leadership to knowledge sharing, knowledge sharing to innovative work behavior, and empowering leadership to innovative work behavior with the mediation of knowledge sharing showed a positive and significant influence relationship.